PELATIHAN PENGAMBILAN FOTO UDARA MENGGUNAKAN UAV UNTUK MENDUKUNG PARIWISATA DI GUNUNG KIDUL - Waluyo, Catur Budi; Dermawan, Denny; Purnomo, M. Jalu (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2020)
The development of unmanned aircraft technology encourage for new infrastructure and development in the tourism sector. Challenges for the development of tourism in Gunungkidul Regency included the development of tourism and cultural villages, access roads to tourism objects, and coastal tourism objects. So, the community service partner was the Gunungkidul Regency Tourism Office. The main objective in this community service activity was to increase knowledge and skills of UAV (Unmanned Aerial Vehicle) to support the development of tourism facilities, particularly in aerial photo taking. The target achieved at this stage was to increase knowledge about UAVs and the ability to control UAV aircraft for taking aerial photographs to support tourism in Gunung Kidul. Increasing ability to control UAVs was done through practice. While increasing knowledge was done through explanation about UAVs. This activity has been able to achieve the expected goals and targets, so that partner can recognize and be able to control the UAV.